Frank O. Gehry : outside in - Greenberg, Jan, 1942-; Jordan, Sandra, (Sandra Jane Fairfax) (New York : DK Ink, 2000)
Photographs and text help profile the life and career of architect Frank O. Gehry.
Includes bibliographical references (p. 46) and index.
School Library Journal starred.
Wilson's Children.
Wilson's Senior High School.
4.7.
4.7
Keywords: Gehry, Frank O., -- 1929- -- Criticism and interpretation -- Juvenile literature; Gehry, Frank O., -- 1929- -- Criticism and interpretation; Gehry, Frank O., -- 1929- -- Criticism; Architecture, Postmodern -- United States -- Juvenile literature; Architecture, Postmodern -- United States; Architecture -- 20th century; Postmodernism -- United States